2016
DOI: 10.5755/j01.ms.22.4.14222
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of CaCO3 Coated Wood Free Paper Usage as Filler on Water Absorption, Mechanical and Thermal Properties of Cellulose-High Density Polyethylene Composites

Abstract: In this study some physical, mechanical and thermal characteristics of high density polyethylene (HDPE) and CaCO3 coated/pigmented wood free paper fiber composites were investigated. The fillers used in this study were uncoated cellulose, 5.8 %, 11.5 %, 16.5 % and 23.1 % CaCO3 coated wood free paper fibers. Each filler type was mixed with HDPE at 40% by weight fiber loading. In this case, the ratio of CaCO3 in plastic composites was calculated as 0 %, 2.3 %, 4.6 %, 6.6 % and 9.2 % respectively. Increased CaCO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
3
8
0
1
Order By: Relevance
“…Later, the extruder was used to blend and extrude the material out of the extruder by a valve to collect the process mixture for the next stage, as shown in Figure 6 for the material preparation process. The control sample was also prepared by blending pure PLA (0 wt%) using the same conditions as done in several other composite studies [49,50]. Due to the capabilities of the extruder that produces limited quantities of the mixtures, the extruded composites were chopped into small pieces (~1 g) and thermally compressed for 5 min using a Carver's press (Carver™ Lab Presses) under 34.47 MPa pressure at 190 • C to produce composite sheets that were used for the mechanical investigation stage.…”
Section: Methodsmentioning
confidence: 99%
“…Later, the extruder was used to blend and extrude the material out of the extruder by a valve to collect the process mixture for the next stage, as shown in Figure 6 for the material preparation process. The control sample was also prepared by blending pure PLA (0 wt%) using the same conditions as done in several other composite studies [49,50]. Due to the capabilities of the extruder that produces limited quantities of the mixtures, the extruded composites were chopped into small pieces (~1 g) and thermally compressed for 5 min using a Carver's press (Carver™ Lab Presses) under 34.47 MPa pressure at 190 • C to produce composite sheets that were used for the mechanical investigation stage.…”
Section: Methodsmentioning
confidence: 99%
“…Cellulose addition for the reinforcement of WPCs were also investigated and significant improvements were obtained [18]. Pesman and Tufan [19] studied the effects of CaCO3 coated wood free paper usage as filler on water absorption, mechanical and thermal properties of cellulose-high density polyethylene (HDPE) composites. They concluded that calcium carbonate presence had increased the water resistance of cellulose fiber-HDPE composites [19].…”
Section: Introduction mentioning
confidence: 99%
“…Pesman and Tufan [19] studied the effects of CaCO3 coated wood free paper usage as filler on water absorption, mechanical and thermal properties of cellulose-high density polyethylene (HDPE) composites. They concluded that calcium carbonate presence had increased the water resistance of cellulose fiber-HDPE composites [19]. However, no research has been conducted on printed waste paper fiber usage and the effects of ink presence on the strength and thermal properties of WPCs.…”
Section: Introduction mentioning
confidence: 99%
“…Natural fibres are inexpensive, also possess some unique properties such as low density to easy to be processed, abundance, no tendency to corrosion and most importantly they promote eco-friendly materials, which are safe to be handled [4,5]. Among popular natural fibres are kenaf, hemp, bamboo and oil palm have widely been discovered by worldwide researchers especially in hard matrix composites such as epoxy and polyester to seek its potential as reinforcements in composite materials.…”
Section: Introduction mentioning
confidence: 99%